2002
DOI: 10.1046/j.1365-2672.2002.01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of vaginal lactobacilli from women in different countries based on 16S rRNA gene sequences

Abstract: Aims: Lactobacilli are widely distributed in food and the environment, and some colonize the human body as commensal bacteria. The aim of this study was to determine the species of lactobacilli that colonize the vagina and compare them with those found in food and the environment. Methods and Results: Thirty‐five Lactobacillus strains from women from seven countries were isolated, and sequences from 16S rRNA genes were determined and compared with existing data in GenBank. A phylogenetic tree was achieved usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
167
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(187 citation statements)
references
References 25 publications
11
167
0
9
Order By: Relevance
“…Furthermore, our study found that L. iners, followed by L. crispatus, was the most predominant species in Chinese women. A study of multinational populations showed that L. crispatus was the most commonly predominant species in most populations (Pavlova et al, 2002). The association between geographical area and Lactobacillus species may be partly explained by genetic factors, because the genetic capacity to produce antimicrobial factors could affect vaginal bacteria including Lactobacillus species (Linhares et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study found that L. iners, followed by L. crispatus, was the most predominant species in Chinese women. A study of multinational populations showed that L. crispatus was the most commonly predominant species in most populations (Pavlova et al, 2002). The association between geographical area and Lactobacillus species may be partly explained by genetic factors, because the genetic capacity to produce antimicrobial factors could affect vaginal bacteria including Lactobacillus species (Linhares et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first microbiological study of the human vagina, lactobacilli have been considered the dominant members of the microbiota of this organ (Doderlein, 1982), a finding that has been further confirmed by several recent metagenomic studies (Biagi et al, 2009;Fettweis et al, 2012;Martín et al, 2014;Pavlova et al, 2002;Song et al, 1999;Verhelst et al, 2004;Vitali et al, 2007;Wilks et al, 2004;Zhou et al, 2004). In total, around 20 different species of lactobacilli have been consistently isolated from the vagina, although only one or two species predominate at a time in a given individual.…”
Section: Introductionmentioning
confidence: 92%
“…In total, around 20 different species of lactobacilli have been consistently isolated from the vagina, although only one or two species predominate at a time in a given individual. Dominant strains vary as a function of race and lifestyle, but strains of Lactobacillus crispatus, Lactobacillus iners, Lactobacillus jensenii and Lactobacillus gasseri are the most frequent (Biagi et al, 2009;Pavlova et al, 2002;Song et al, 1999;Verhelst et al, 2004;Vitali et al, 2007;Wilks et al, 2004;Zhou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…С использованием метаге-номного анализа установлено наличие в ваги-нальном микробиоме около 20 видов лактоба-цилл [8]. При этом доминирующими являются четыре вида группы Lactobacillus acidophilus: L. crispatus, L. jensenii, L. gasseri и L. iners [9].…”
Section: вагинальный микробиомunclassified